Fermentation of palm kernel expeller using local fungal enzymes for production potential prebiotics - Chen, Wei Li (2014)
The rapid expansion of livestock industry to meet the increasing demand for animal protein has stimulated the search for appropriate agro by-products as alternative feed resources. Among the available by-products, palm kernel expeller (PKE) has been identified to be of great potential, because large quantity of this by-product from the palm oil industry is being produced annually in Malaysia. Many attempts have been made to reduce the high non-starch polysaccharides (NSP) of PKE to a tolerable level for monogastric animal, particularly poultry diets. This includes the use of exogenous enzymes, which has been proven rather successful in reducing the NSP contents, but when the enzyme treated PKE was fed to the animal, results in term of animal performance was inconsistent. In addition, scanty research data suggested that PKE can be a potential source for prebiotic instead of only as a source of dietary energy for monogastric animals. Thus, to overcome the current over-dependent on the use of commercial enzymes, which are normally imported at high cost to hydrolyse the NSP, the primary objective of this thesis was to increase the production of prebiotic oligosaccharides from PKE by using enzyme produced by indigenous fungi isolated from PKE itself.